Peptide Ligands to Human Immunodeficiency Virus Type 1 gp120 Identified from Phage Display Libraries - Ferrer, Marc (American Society for Microbiology, 1999)
We have used phage-displayed peptide libraries to identify novel ligands to the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein gp120. Screening of libraries of random 12-mers, 7-mers, and cyclic 9-mers produced two families of gp120 binding peptides. Members of a family with the prototype sequence RINNIPWSEAMM (peptide 12p1) inhibit the interaction between gp120 and both four-domain soluble CD4 (4dCD4) and monoclonal antibody (MAb) 17b, a neutralizing antibody that covers the chemokine receptor binding surface on gp120. Peptide 12p1 inhibits the interaction of 4dCD4 with gp120 from three different HIV strains, implying that it binds to a conserved site on gp120. Members of a second family of peptides, with the prototype sequence TSPYEDWQTYLM (peptide 12p2), bind more weakly to gp120. They do not detectably affect its interaction with 4dCD4, but they enhance its binding to MAb 17b. A common sequence motif in the two peptide families and cross-competition for gp120 binding suggest that they have overlapping contacts. Their divergent effects on the affinity of gp120 for MAb 17b may indicate that their binding stabilizes distinct conformational states of gp120. The functional properties of 12p1 suggest that it might be a useful lead for the development of inhibitors of HIV entry.